Implementation of the Concept of Moral Education in the Book of Alala Tanalul Ilma in the Era of Society 5.0 - Khabib Solihin; Muhammad Ulil Albab (The Institute of Research and Service Community IPMAFA Pati, 2022)
The development of technology and science in the era of society 5.0 has a positive impact on the development of human civilization and also leaves some homework that needs to be a common concern, including those related to morals. The development of technology provides a free and spacious space for anyone to communicate and behave in cyberspace. This if not guided by morals and good behavior patterns will lead to a decrease in morals in attitude and communication. Imam Azzarnuji in the book of alala tanalil ilma provides a very relevant moral education guide to be used as a guide for behavior in the era of society 5.0. This research is a descriptive qualitative research that examines the book of alala tanalul ilma by Imam Azzarnuji. This study concludes that in the Nadhom Kitab alala tanalul ilma the concept of moral education is implied which can be implemented in the era of society 5.0. The results of the study show that there are 5 (five) classifications of moral education in the Alala Tanalul Ilma book, namely morals in making friends, communication morals, morals in studying, morals of knowledgeable people, and morals to teachers and parents. The development of science and technology contained in the era of society 5.0 must be balanced with strengthening the morals of Muslims. So that the development of technology and science is able to realize the benefit of life and prevent humans from being harmed. The results of this study are expected to be able to become one of the ummah's reference centers for references in upholding good morals in their lives for the achievement of the benefit of life.